The elusive nature of the Rheic Ocean suture in SW Iberia. Issue 12 (16th December 2015) - Pérez‐Cáceres, I.; Martínez Poyatos, D.; Simancas, J. F.; Azor, A.
Abstract: The Rheic Ocean suture resulted from pre‐Carboniferous oceanic subduction followed by Late Devonian‐Carboniferous Variscan collision. In SW Iberia, this suture has been classically located along the boundary between the Ossa‐Morena and South Portuguese Zones based on the presence of three units: (i) a conspicuous metamafic unit (Beja‐Acebuches) that crops out along this boundary and has been interpreted as a pre‐Carboniferous Rheic Ocean ophiolite; (ii) a low‐grade metasedimentary unit with minor mid‐ocean ridge basalt‐like lithologies (Pulo do Lobo unit), thought to represent a Rheic Ocean subduction‐related accretionary prism; and (iii) the allochthonous Cubito‐Moura unit that contains high‐pressure and ophiolitic‐like rocks. We report new structural and geochronological data that allow us to reinterpret the origin and internal structure of the Beja‐Acebuches and the Pulo do Lobo units. Thus, both the Beja‐Acebuches protoliths and the Pulo do Lobo metabasalts would have been formed in the context of an intracollisional extensional stage that interrupted the Variscan collision at early Carboniferous time, after the Rheic Ocean consumption, and the first continental collision. Later on, collision was resumed in an oblique left‐lateral regime that gave way to coeval frontal (folds and thrusts) and lateral (shear zones and strike‐slip faults) structures, with variable pressure‐temperature conditions and space distribution along time. As a consequence of the superposition of transtension and complex transpression, the Rheic suture in SW Iberia has an obscure nearly cryptic appearance. Key Points: Variscan evolution of the Ossa‐Morena/South Portuguese zone boundary Early carboniferous transtension and mafic magmatism in SW Iberia Transpression produced spatial and temporal strain partitioning in SW Iberia